Dzyaloshinskii-Moriya anisotropy and nonmagnetic impurities in the s= 1/2 kagome system ZnCu3 (OH) 6 Cl2 - Ioannis Rousochatzakis; Salvatore R. Manmana; Andreas M. Lauchli; Bruce Normand; Frederic Mila (2009)
Motivated by recent nuclear magnetic resonance experiments on ZnCu3 (OH) 6 Cl2, we present an exact-diagonalization study of the combined effects of nonmagnetic impurities and Dzyaloshinskii-Moriya (DM) interactions in the s=1/2 kagome antiferromagnet. The local response to an applied field and correlation-matrix data reveal that the dimer freezing which occurs around each impurity for D=0 persists at least up to D/J sqar;0.06, where J and D denote, respectively, the exchange and DM interaction energies. The phase transition to the (Q=0) semiclassical 120°state favored at large D takes place at D/Jsqar;0.1. However, the dimers next to the impurity sites remain strong up to values D∼J, far above this critical point, and thus do not participate fully in the ordered state. We discuss the implications of our results for experiments on ZnCu3 (OH) 6 Cl2. © 2009 The American Physical Society.